Effects of urate-lowering agents on arrhythmia vulnerability in post-infarcted rat hearts - Tsung-Ming Lee; Shinn-Zong Lin; Nen-Chung Chang (Elsevier, 2016)
Hyperuricemia has been shown to be associated with ventricular arrhythmias. However, the mechanisms remained unknown. We assessed whether different urate-lowering agents can attenuate arrhythmias through lowering urate itself or inhibiting xanthenes oxidize (XO) activity in infarcted rats. Male Wistar rats after ligating coronary artery were randomized to either allopurinol, or febuxostat, chemically unrelated inhibitors of XO, benzbromarone or vehicle for 4 weeks. Post-infarction was associated with increased oxidant stress, as measured by myocardial superoxide, isoprostane, XO activity and dihydroethidine fluorescence staining. Measurement of myocardial norepinephrine levels revealed a significant elevation in vehicle-treated infarcted rats compared with sham-operated rats. Sympathetic hyperinnervation was blunted after administering both XO inhibitors, assessed by immunofluorescent analysis, Western blotting and real-time quantitative RT-PCR. Besides, the XO inhibitors-attenuated nerve growth factor levels were reversed in the presence of peroxynitrite generator. Arrhythmic scores in the XO inhibitors-treated infarcted rats were significantly lower than that in vehicle. For similar levels of urate lowering, the uricosuric agent benzbromarone had no beneficial effects on oxidative stress, sympathetic hyperinnervation or arrhythmia vulnerability. Chronic use of XO inhibitors, but not uricosuric agent, down-regulated sympathetic innervation probably through a superoxide-dependent pathway and plays a role in the beneficial effect on arrhythmogenic response.